2016
DOI: 10.1038/srep34581
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin and Nox2 regulate NF-κB by modifying thioredoxin-1 redox-state

Abstract: The reactive-oxygen-species-(ROS)-generating-enzyme Nox2 is essential for leukocyte anti-microbial activity. However its role in cellular redox homeostasis and, consequently, in modulating intracellular signaling pathways remains unclear. Herein, we show Nox2 activation favors thioredoxin-1 (TRX-1)/p40phox interaction, which leads to exclusion of TRX-1 from the nucleus. In contrast, the genetic deficiency of Nox2 or its pharmacological inhibition with apocynin (APO) results in reductive stress after lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
(69 reference statements)
5
25
0
2
Order By: Relevance
“…Apocynin has been widely evaluated in experimental research as an antioxidant agent [ 17 19 ]. In literature several apocynin dosages have been used, ranging from 4 mg/kg/day [ 49 ] to 100 mg/kg/day [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apocynin has been widely evaluated in experimental research as an antioxidant agent [ 17 19 ]. In literature several apocynin dosages have been used, ranging from 4 mg/kg/day [ 49 ] to 100 mg/kg/day [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apocynin, a drug isolated from the medicinal herb Picrorhiza kurroa [ 16 ], is considered an antioxidant agent which inhibits NADPH oxidase activity and improves ROS scavenging [ 17 19 ]. We have previously observed that apocynin reduces myocardial oxidative stress without changing NADPH oxidase activity in diabetic hypertensive rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In macrophages, upon stimulation with lipopolysaccharides, p40 phox interacts with oxidized Trx1, preventing its reduction and its ability to bind with NF-κB. On the other hand, inhibition of Nox2 by apocyanin promoted reduction and nuclear translocation of Trx1, thus enhancing its ability to bind to NF-κB and promoting transcription of several inflammatory mediators during sepsis [21]. Cytoplasmic binding of Trx1 to IκB prevents degradation of IκB and inhibits nuclear translocation of NF-κB in HSC-1 cells, thus decreasing its transcriptional activity [22].…”
Section: Specific Targets Of Trx1mentioning
confidence: 99%
“…Para poder relacionar essa produção de espécies reativas de oxigênio com a liberação de NETs, utilizamos Apocinina, um inibidor farmacológico da enzima NADPH oxidase. Pré-tratamos as células com Apocinina na concentração de 300uM, por trinta minutos, condição em que já é descrita por inibir a produção de espécies reativas de oxigênio (Trevelin et al, 2016) e avaliamos a produção de NETs. Observamos que a inibição farmacológico da produção de espécies reativas de oxigênio prejudicou a geração de NETs induzida por Chikungunya (Fig.…”
Section: O Vírus Chikungunya Induz Uma Netose Dependente De Espécies unclassified